2011
DOI: 10.1021/jp202849c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of Ferromagnetism in ZnO Porous Microspheres by Systematic Investigations of the Thermal Decomposition of Zn5(OH)8Ac2·2H2O to ZnO

Abstract: In this paper, thermogravimetric analyses, Fourier transform infrared spectra, X-ray powder diffraction, photoluminescence, electron paramagnetic resonance, and superconducting quantum interference device magnetometer are applied to observe the thermal decomposition of Zn5(OH)8Ac2·2H2O to ZnO for understanding the origin of room temperature ferromagnetism in ZnO porous microspheres. The results show that both zinc vacancies and shallow donors induced by hydrogen may play an important role in triggering magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 56 publications
6
36
0
1
Order By: Relevance
“…25,29 Total weight loss values of 31-38% have been reported for LBZA in the literature. 26,29,31,37 In this study, the weight losses observed in the presence of 0.2 mM EM-12 and above, supported the presence of LBZA in the samples (Fig. 2b).…”
Section: Delay/suppression Of Zno Formation By Em-12supporting
confidence: 76%
“…25,29 Total weight loss values of 31-38% have been reported for LBZA in the literature. 26,29,31,37 In this study, the weight losses observed in the presence of 0.2 mM EM-12 and above, supported the presence of LBZA in the samples (Fig. 2b).…”
Section: Delay/suppression Of Zno Formation By Em-12supporting
confidence: 76%
“…layered basic zinc acetate, LBZA), koji zatim žarenjem prelazi u ZnO zadržavajući listićavu morfologiju LBZA. [5][6][7][8][9][10] Hidrotermalna sinteza alternativni je pristup pripravi slojeva sličnih morfologija, [11][12][13][14] no preliminarna istraživanja pokazuju da su takvi slojevi vrlo prhki i znatno slabije vezani na nemodificiranu podlogu od slojeva iz metanolne otopine. Prethodno 15 su ustanovljeni optimalni uvjeti za dobivanje karakteristične cvjetaste morfologije ZnO.…”
Section: Uvodunclassified
“…The details regarding the growth process of ZnO nanoplatebuilt hollow microspheres are similar to those reported in our previous study. 23 In a typical procedure, 10 mmol of Zn(CH 3 COO)·2H 2 O), 10 mmol of C 6 H 12 N 4 , and 1 mmol of C 6 H 5 Na 3 O 7 ·2H 2 O were dissolved in 100 mL of distilled water. The solution was then stirred for 30 min.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%